THE ABILITY OF GREEN ENTREPRENEURIAL ORIENTATION AND SUPPLY CHAIN MANAGEMENT TO IMPACT THE SUSTAINABILITY PERFORMANCE OF SMES IN THE GRESIK DISTRICT - Narto, Narto; Radianto, Wirawan Endro Dwi; Wahjudono, Denny Bernardus Kurnia (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
This research explores the sustainability performance phenomenon, focusing on green entrepreneurial orientation, innovation, and supply chain management. The research population consists of entrepreneurial SMEs in the Gresik District. The research sample of 324 respondents was selected using the purposive sampling technique, questionnaires were distributed through online media, and then data analysis was carried out using the PLS technique approach with Smart PLS software. The research revealed that green entrepreneurial orientation significantly impacts green innovation, sustainability performance, and supply chain management. Furthermore, green innovation has a considerable positive impact on sustainability performance, and green supply chain management significantly impacts sustainability performance. Furthermore, green innovation mediates a significant positive relationship between green entrepreneurial orientation and sustainability performance. Additionally, green supply chain management mediates a significant positive relationship between green entrepreneurial orientation and sustainability performance. Contribution This research assists entrepreneurs in exploring environmentally friendly factors to improve the sustainable performance of SMEs to enhance competitiveness. JEL: C12, L26, Q56.